Emotional Furniture Design For The Elderly：How To Make Design Connect To End-Users - Lu, Jing; Musdi, Shanat (UNIMAS Publisher, 2025)
As the problem of an aging society becomes increasingly serious, the emotional needs and quality of life of the elderly are receiving more and more attention. Furniture is not only closely related to people's daily lives, but also shows the emotional pursuits and personality characteristics of users during use. Therefore, in order to narrow the distance between elderly furniture and users, it is necessary to use the concept of emotional design, and then design furniture products with spiritual care and emotional satisfaction characteristics according to the physiological and psychological characteristics of the elderly and their emotional needs. This paper aims to explore how to improve the comfort and emotional resonance of furniture used by the elderly through emotional design methods. Through empathetic design and metaphorical techniques, we designed furniture that can arouse emotional resonance and psychological memory to meet the social and emotional needs of the elderly in environments such as reading rooms. The ultimate goal is to design furniture that is both practical and that can give emotional support and spiritual satisfaction to the elderly, so that they can feel the care and respect of society in their later years.